THE CULT OF THE TREE AS A REMAINDER OF PAGANISM IN THE FOLK TRADITION OF KOSOVO AND METOHIJA. MEMORY OF THE „HOLY PINE“ IN THE GORNJE NERODIMLJE IN THE TRADITION OF THE CONVOCATION (Heritage, 2021)
SUMMARYFolk tradition in general is very often associated with natural entities, drawing its strength from believing in their magical properties. The cult of tree is one of the remnants of pagan elements that the Church accepted, because the people resisted all church proclamations, prohibitions and with their perseverance in respecting the cult of tree in all segments of life managed to preserve it. In that endeavor, the tree was given a new semantic meaning, which resulted in its partial imposition on the church. There are numerous examples of respect for the cult of the tree, which is noticeable within the multitude of customs and rituals that are still performed in rural areas throughout Serbia. In the Serbian folk tradition, a pine tree is often considered sacred if it is planted in a significant place or by an important person. A prominent example of such a belief can be found in the village of Gornje Nerodimlje, where the pillar of parliamentary customs was a pine tree, which, according to the beliefs of today's population, was personally planted by King Milutin and sung in the folk song "Oj, bore sabore." Given the current circumstances in which the Serb population was completely evicted from Gornje Nerodimlje, thus preventing them from accessing their long-guarded and respected sanctities, the Easter gathering, which many locals describe as the happiest holiday of their lives in Kosovo and Metohija, is destroyed along with the trees which represented a central elements of this tradition. Therefore, it is especially important to preserve this tradition from the memory of older locals. The semantic connection of the song to the pine tree certainly opens the possibility of analyzing the melodies in which the musical elements of depicting the meaning of the text can be noticed. In the minds of the displaced population of Gornji Nerodimlje, the song "Oj, bore sabore" is dedicated to King Milutin's pine tree. Although according to the dilemmas presented, we cannot claim that this tree has always been known as a handicraft of this historical figure, nor that the song was sung in the honor of that tree, we cannot deny that ancient tradition to people who lived in Gornje Nerodmlje or their descendants.
Keywords: cult of trees, Gornje Nerodimlje, King Milutin’s pine tree, Kosovo and Metohia, folk tradition